Development of conventional PCR and a Real-Time PCR assay to choose the most suitable method for residual DNA identification of Beluga, Huso huso, in concrete fish ponds - Esmaeil Noghanchi Sabet; Shirin Jamshidi; Ali Bani (Caspian Journal of Environmental Sciences)
A unique research was developed to achieve an effective and efficient method for tracing and identifying Beluga sturgeon species, Huso huso using eDNA in concrete fish ponds. Sampling was performed from the water of the Beluga pond and fixed with precipitation premix solution. DNA was extracted from fixed water, and fin tissue of Beluga. Three short fragments were selected from a nuclear and two mitochondrial genes region of Beluga DNA. The specificity of primers was checked by conventional PCR for Beluga with fin tissue DNA samples. In this study, two conventional methods of molecular identification were performed on residual DNA samples of fish pond water and fin tissue, exhibiting that they were not suitable for measuring the residual DNA of Beluga in fish ponds due to the low rate of DNA. PCR amplification of sturgeon’s DNA of mitochondrial COΙ gene in third PCR primers was successful in low level of DNA extracted from water column and sediment by conventional and Quantitative PCR. The linear relationship between the threshold cycle (ct) value and Beluga DNA concentration was measured by the Mini-Barcoding quantitative Real-Time PCR. DNA samples of fish ponds generated a uniform curve in water column and sediment. In identifying residual DNA in the Picogram level of Beluga pond, SYBER Green Real-Time PCR method can be an acceptable method for barcoding with high efficiency compared to other methods such as conventional PCR method and non-invasive which is advantageous for the conservation of critically endangered sturgeons such as Beluga. This research results can also be used as a model for tracing fish species in rivers and seas.